A confirmatory factor analysis of social anxiety scale for adolescence (SAS-A) in Indonesian form - Apriliana, I Putu Agus; Suranata, Kadek (Konselor, 2019)
Social anxiety in adolescence can interfere with the development process. Detecting of social anxiety is very important to preventive strategy. Purpose of this study is knowing fit criteria of the SAS-A in the Indonesian version. SAS-A in Indonesian version is tool to detect social anxiety in Indonesian adolescence. This study used quantitative research. Total of participants is 172 with 74 male and 98 female. Data collected by excel in google form and was analysis using the CFA approach. CFA is used for evaluation and constructs validation of SAS-A in Indonesian version using Amos 20. The Results of this study is Â SAS-A in Indonesian version after being analysis factor confirmatory, it known that fit of 11 item and 7 item have been removed because it is not fit to measure construct factor. These findings suggest that the Indonesia version of the SAS-A is a developmentally appropriate instrument that can be used to examine adolescent social anxiety development. Limitations and suggestions for future research are discussed